BMP9 induces osteogenesis and adipogenesis in the immortalized human cranial suture progenitors from the patent sutures of craniosynostosis patients. Issue 11 (4th May 2017) - Song, Dongzhe; Zhang, Fugui; Reid, Russell R.; Ye, Jixing; Wei, Qiang; Liao, Junyi; Zou, Yulong; Fan, Jiaming; Ma, Chao; Hu, Xue; Qu, Xiangyang; Chen, Liqun; et al.
Abstract: The cranial suture complex is a heterogeneous tissue consisting of osteogenic progenitor cells and mesenchymal stem cells (MSCs) from bone marrow and suture mesenchyme. The fusion of cranial sutures is a highly coordinated and tightly regulated process during development. Craniosynostosis is a congenital malformation caused by premature fusion of cranial sutures. While the progenitor cells derived from the cranial suture complex should prove valuable for studying the molecular mechanisms underlying suture development and pathogenic premature suture fusion, primary human cranial suture progenitors (SuPs) have limited life span and gradually lose osteoblastic ability over passages. To overcome technical challenges in maintaining sufficient and long‐term culture of SuPs for suture biology studies, we establish and characterize the reversibly immortalized human cranial suture progenitors (iSuPs). Using a reversible immortalization system expressing SV40 T flanked with FRT sites, we demonstrate that primary human suture progenitor cells derived from the patent sutures of craniosynostosis patients can be efficiently immortalized. The iSuPs maintain long‐term proliferative activity, express most of the consensus MSC markers and can differentiate into osteogenic and adipogenic lineages upon BMP9 stimulation in vitro and in vivo . The removal of SV40 T antigen by FLP recombinase results in a decrease in cell proliferation and an increase in the endogenous osteogenic and adipogenic capability in the iSuPs. Therefore, the iSuPs should be a valuable resource to study suture development, intramembranous ossification and the pathogenesis of craniosynostosis, as well as to explore cranial bone tissue engineering.